Kinematic factors affecting the score in archery: using SEM - Hah, C. K.; Park, J.; Yi, J. H.; An, H. S. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The shooting movements of Archery are paths of continuous and causal movements. Structural equation modeling (SEM) grows out of and serves purposes similar to multiple regression and may be used as a more powerful alternative to multiple regression, path analysis, factor analysis, time series analysis, and analysis of covariance. Some reachers in marketing have used SEM to analyze data deprived from experiments. The purpose of this study was to investigate the structural equations between kinematic factors affecting score during backtension which was basic and important in archery. METHOD: A male subject(21yrs ,82kg, 185cm) is the second archer ranked in the world authorized by FITA. 60 shootings were captured with seven infrared cameras (MCU-240, Qualisys Inc., Switzerland) and SEM(DoG=4. Size=60) of data was analyzed with LISEL8.80. DISCUSSION: Model being tested was accepted by means of GoFS, and ASJ1 (Angle of scapular joint during phase1:anchoring-release) and AVSJ2 (Angular velocity of scapular joint during phase2:release-follow through) are statistically significant(/t/>1.96) above two equations. Y(ASJ2) = 0.32 * X1(ASJ1) and Y(AVSJ2) = 0.69 * X1(ASJ2) - 0.17* X2 (ASJ1) are significant equations. SEM can be used to analyze experimentlal data and is a useful tool for various analyses.